2017
DOI: 10.3892/ijo.2017.4034
|View full text |Cite|
|
Sign up to set email alerts
|

HNF1A-AS1 promotes growth and metastasis of esophageal squamous cell carcinoma by sponging miR-214 to upregulate the expression of SOX-4

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common malignancies in the world, marked by dysphagia and weight loss, bringing great suffering to patients. HNF1A‑AS1 (HAS1), a long non-coding RNA (lncRNA), has been identified prevalently involved in various human cancers. However, the exact effects and molecular mechanisms of HAS1 in ESCC progression are still elusive. In this study, upregulated expression of HAS1 was detected in ESCC tissues and four human ESCC cell lines (KYSE70, KYSE450, EC109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…HNF1A-antisense 1 (HNF1A-AS1) is the sole lncRNA reported to modulate VEGF thus far. Recently, Wang reported that the knockdown of HAS1 suppressed the expression of VEGF in ESCC cells [ 123 ]. However, direct supporting evidence that HAS1 inhibits angiogenesis requires further studies.…”
Section: Involvement Of Lncrnas In the Hallmarks Of Cancermentioning
confidence: 99%
“…HNF1A-antisense 1 (HNF1A-AS1) is the sole lncRNA reported to modulate VEGF thus far. Recently, Wang reported that the knockdown of HAS1 suppressed the expression of VEGF in ESCC cells [ 123 ]. However, direct supporting evidence that HAS1 inhibits angiogenesis requires further studies.…”
Section: Involvement Of Lncrnas In the Hallmarks Of Cancermentioning
confidence: 99%
“…Interestingly, SOX4 was reported to be a direct target gene of miR-214 and SOX4 served as an important oncogene to promote ESCC development. 19,26 Here, we found SOX4 was elevated in ESCC tissues and patients with high SOX4 expression had shorter overall survival rates. These findings were consistent with previous reports.…”
Section: Dovepressmentioning
confidence: 60%
“…Previous study identified that SOX4 was a direct downstream gene of miR-214 in ESCC cells. 19 We found that SOX4 was up-regulated in multiple cancers including ESCC in the GEDS database ( Figure 7A). 20 Similarly, there was a remarkable increase of SOX4 mRNA expression in ESCC tissues based on the analysis of GEPIA database and Oncomine (https:// www.oncomine.org/) ( Figure 7B and C).…”
Section: Mir205hg Upregulates Sox4 Expression By Mir-214mentioning
confidence: 90%
“…For example, lncRNA sponging of miR-224, TUSC7 suppresses chemotherapeutic resistance in ESCC cells by modulating the DESC1/EGFR/AKT pathway [ 12 ]. And by sponging miR-214, LncRNA HNF1A-AS1 promotes ESCC by upregulating SOX-4 expression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%